Comparison of Amiodarone and Propafenone in Blanking Period after Radiofrequency Catheter Ablation in Patients with Atrial Fibrillation: A Propensity Score-Matched Study. (26th June 2020) - Huang, RongDa; Lin, JingJing; Gong, KeZeng; Chen, LiangLong; Fan, Lin; Zhang, FeiLong; Zhang, Yan; Chen, XueHai; Xu, Zhe
Abstract : Background. Amiodarone and propafenone are commonly used to maintain sinus rhythm in patients with atrial fibrillation (AF). However, it is not known which one is better in reducing early recurrence (ER) during the blanking period (the first three months after catheter ablation). Objective. To compare the efficacy and safety of amiodarone and propafenone in reducing ER during the blanking period after radiofrequency catheter ablation (RFCA) in AF patients. Materials and Methods. A total of 694 patients who underwent their first RFCA between May 2014 and May 2018 were enrolled in this retrospective study. Subsequently, 202 patients were excluded according to the exclusion criteria. The remaining 492 patients were divided into two groups based on the choice of antiarrhythmic drugs (AADs) (amiodarone or propafenone) in the blanking period. The primary outcomes were incidence of ER and AAD-associated adverse effects during the blanking period after RFCA. Propensity score matching (PSM) analyses were used to compare the outcomes of the two groups while controlling for confounders. Results. Among the 492 patients who took AADs in the blanking period (187 amiodarone and 305 propafenone), PSM selected 135 unique pairs of patients with similar characteristics. Amiodarone was associated with a lower ER incidence rate (23.7% versus 48.9%, p < 0.001 ) and a similar rate of AAD-associated adverse effects (2.1% versus 1.5%, p = 0.652 ). Treatment with amiodarone in the blanking period was significantly associated with a lower ER incidence rate compared to treatment with propafenone (HR = 0.416, 95% CI 0.272–0.637, p < 0.001 ). Conclusions. Compared with propafenone, amiodarone was associated with a lower ER incidence rate, and they had similar rates of AAD-associated adverse effects. Treatment with amiodarone in the blanking period was shown to be more effective in reducing ER than propafenone.